The Tension between Divine Sovereignty and Human Agency in Pentecostal Theology: Miracles, Healing, and the ‘Word of Faith’ Movement - Upa Silaen; Ibiang O. Okoi; Foret Nicholson (DIEGESIS: Jurnal Teologi Kharismatika, 2025)
Pentecostal theology has long emphasized the dynamic interplay between divine sovereignty and human agency, particularly in the realms of miracles, healing, and faith. However, the rise of the Word of Faith movement with its teachings on “claiming” blessings through faith has intensified theological and pastoral tensions within Pentecostalism. This study examines the biblical, historical, and theological foundations of Pentecostal views on healing, contrasting classical Pentecostal perspectives with the more controversial Word of Faith approach. It further analyzes how this core tension manifests in the gendered dynamics of global healing ministries, where women’s Spirit-empowered authority often exists in paradoxical tension with institutional patriarchy. While early Pentecostals like William Seymour and Charles Parham viewed healing as a sovereign act of God, albeit responsive to faith, later figures such as Kenneth Hagin and Kenneth Copeland framed faith as an almost mechanistic force that obligates divine intervention. The paper explores key biblical passages (e.g., Mark 5:34, James 5:14-16, and 2 Corinthians 12:7-10) to assess whether the Word of Faith movement aligns with Scripture or risks reducing God’s power to human manipulation. It also engages critiques from Pentecostal scholars (e.g., Gordon Fee, Amos Yong) who warn against the movement’s potential for spiritual abuse, particularly in its tendency to blame believers for unanswered prayers. The study further analyzes pastoral implications, including theodicy concerns when healing does not occur, the ethical pitfalls of prosperity-centered preaching, and the need for an ecclesial practice that affirms the Spirit’s sovereign distribution of healing gifts across gender lines. Ultimately, the paper argues for a balanced Pentecostal theology that upholds both God’s sovereignty and human responsibility, one that makes theological space for the full exercise of charismatic gifts by all believers, thereby avoiding the extremes of passive fatalism and presumptive “faith formulas.” By reclaiming the early Pentecostal emphasis on the Spirit’s unpredictability and the biblical theology of suffering, and by confronting its own gendered paradoxes, contemporary Pentecostalism can navigate these tensions with greater theological integrity and pastoral sensitivity. Keywords: divine healing; divine sovereignty; pentecostal theology; word of faith movement Abstrak Teologi Pentakosta sejak lama menekankan keterkaitan dinamis antara kedaulatan ilahi dan agensi manusia, khususnya dalam ranah mujizat, kesembuhan, dan iman. Namun, kemunculan gerakan Word of Faith dengan ajarannya tentang “mengklaim” berkat melalui iman telah memperuncing ketegangan teologis dan pastoral di dalam Pentakostalisme. Studi ini menelaah dasar biblika, historis, dan teologis dari pandangan Pentakosta tentang kesembuhan, dengan membandingkan perspektif Pentakosta klasik dan pendekatan Word of Faith yang lebih kontroversial. Studi ini juga menganalisis bagaimana ketegangan mendasar tersebut termanifestasi dalam dinamika pelayanan kesembuhan di berbagai konteks global yang bercorak gender, di mana otoritas perempuan yang diberi kuasa oleh Roh seringkali berada dalam ketegangan paradoksal dengan struktur patriarki institusional. Sementara para Pentakosta awal seperti William Seymour dan Charles Parham memandang kesembuhan sebagai tindakan kedaulatan Allah, meskipun tanggap terhadap iman, tokoh-tokoh kemudian seperti Kenneth Hagin dan Kenneth Copeland membingkai iman sebagai suatu kekuatan yang hampir mekanistik yang mewajibkan intervensi ilahi. Artikel ini mengeksplorasi bagian-bagian Alkitab kunci (misalnya Markus 5:34; Yakobus 5:14–16; dan 2 Korintus 12:7–10) untuk menilai apakah gerakan Word of Faith sejalan dengan Kitab Suci atau justru berisiko mereduksi kuasa Allah menjadi manipulasi manusia. Tulisan ini juga berinteraksi dengan kritik para sarjana Pentakosta (misalnya Gordon Fee, Amos Yong) yang memperingatkan potensi penyalahgunaan rohani dalam gerakan tersebut, khususnya kecenderungannya menyalahkan orang percaya atas doa yang tidak dijawab. Studi ini selanjutnya menganalisis implikasi pastoral, termasuk persoalan teodise ketika kesembuhan tidak terjadi, jebakan etis dari pengkhotbahan yang berpusat pada kemakmuran, serta kebutuhan akan praktik gerejawi yang menegaskan distribusi kedaulatan karunia kesembuhan oleh Roh melintasi batas-batas gender. Akhirnya, artikel ini berargumen bagi suatu teologi Pentakosta yang seimbang yang menegakkan baik kedaulatan Allah maupun tanggung jawab manusia yang memberi ruang teologis bagi pelaksanaan penuh karunia-karunia karismatik oleh semua orang percaya, sehingga menghindari ekstrem pasif fatalistik maupun “rumus iman” yang presumtif. Dengan memulihkan penekanan Pentakosta awal pada ketidak-terdugaan Roh dan teologi penderitaan yang alkitabiah, serta dengan menghadapi paradoks gendernya sendiri, Pentakostalisme kontemporer dapat menavigasi ketegangan ini dengan integritas teologis dan kepekaan pastoral yang lebih besar. Kata kunci: kesembuhan ilahi; kedaulatan ilahi; teologi Pentakosta; gerakan Word of Faith